The analysis of the iran”s air transportation problems (case study : Mehrabad International Airport) - mohsen saghaei (تحقیقات کاربردی علوم جغرافیایی)
Abstract In present century the air transportation has had a very important role in relations between different countries of the world ,as exchanging of culture, showing the economical and military power and speeding the vital affairs of a country and in this case airports form a very critical role in the Air Transportation system An airport is the most infrastructural part of the transportation industry in each country. Therefore, recognizing the problems of this sector of the aviation industry is effective on expediting activities related to the transportation of passengers, the development of the flight network, the growth of the physical airport, reduction in air accidents and problems caused by the proximity to residential areas (colliding with residential areas and noise pollution). In this regard, the aim of the present study is to investigate the problems of Mehrabad International Airport as the most important airport for domestic flights from the aerodrome point of view and the flight network based on standard indices of the national aviation industry. Therefore, among the experts of the aviation industry (pilots, officials and personnel working at Mehrabad Airport), 240 individuals were selected as the sample and a researcher made questionnaire was distributed among them. The application of factor analysis model and SPSS and Lisrel software revealed that the most important problems of Mehrabad Airport are proximity to residential areas, causing noise pollution for residents around the airport, adjacent to the military airport, lack of proper distance from other airports, and its role as flight origin for domestic flights in the Iran’s national airline, totally explain 83.79 % of the common variance. Other variables have not been able to justify significant variance.